2019
DOI: 10.1186/s13071-019-3426-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic screening of the ‘Kurz-box’ of chemicals identifies two compounds (BLK127 and HBK4) with anthelmintic activity in vitro against parasitic larval stages of Haemonchus contortus

Abstract: Background Due to anthelmintic resistance problems, there is a need to discover and develop new drugs for the treatment and control of economically important and pathogenic nematodes of livestock animals. With this focus in mind, we screened 236 compounds from a library (called the ‘Kurz-box’) representing chemically diverse classes such as heterocyclic compounds (e.g. thiazoles, pyrroles, quinolines, pyrimidines, benzo[1,4]diazepines), hydoxamic acid-based metalloenzyme inhibitors, peptidomimetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…YAK308 induced a “curved” phenotype in ~90% of xL3s ( Figure 1 ), distinct to phenotypes in all control wells (0.5% DMSO, monepantel and moxidectin). Although the curved phenotype seemed to be unique, a similar phenotype was observed previously in xL3s and L4s of H. contortus exposed in vitro to compound HBK4—an active benzimidazole-derivative from a previous chemical collection from the Kurz-laboratory [ 19 ].…”
Section: Resultssupporting
confidence: 62%
“…YAK308 induced a “curved” phenotype in ~90% of xL3s ( Figure 1 ), distinct to phenotypes in all control wells (0.5% DMSO, monepantel and moxidectin). Although the curved phenotype seemed to be unique, a similar phenotype was observed previously in xL3s and L4s of H. contortus exposed in vitro to compound HBK4—an active benzimidazole-derivative from a previous chemical collection from the Kurz-laboratory [ 19 ].…”
Section: Resultssupporting
confidence: 62%
“…The nematode eggs were collected by differential sieving through three stacked sieves as described by Varady et al (2007) and recovered with a sucrose flotation technique followed by washing in tap water. The L1s were produced from isolated eggs cultivated in tap water at 27 • C for 48 h, while the L3s were cultivated from eggs in humidified feces from infected sheep at 27 • C for 1 week (Nguyen et al, 2019).…”
Section: H Contortus Strains and Culturingmentioning
confidence: 99%
“…Interestingly, compound BLK127 exerted a phenotype that was similar to a recently described lethal evisceration phenotype. HBK4, a benzimidaxole derivative, was markedly more potent on L4s than L3s [71]. In a consequent study, BLK127 was found to decrease the viability of adult H. contortus both in sensitive and resistant strains and showed no hepatotoxic effect, even at the highest concentration tested while HBK4 had no impact on the viability of adults and exhibited significant hepatotoxicity.…”
Section: Synthetic Compoundsmentioning
confidence: 96%